岐阜県熊石洞産の後期更新世のヤベオオツノジカとヘラジカの化石（その２）体幹骨・肢骨 - 樽野, 博幸; 3640; タルノ, ヒロユキ; 河村, 善也; 3641; カワムラ, ヨシナリ; 石田, 克; 3642; イシダ, シノグ; 奧村, 潔; 3643; オクムラ, キヨシ; et al. (2017)
中部日本に位置する熊石洞は，数多くの後期更新世の哺乳類化石を産出している．その中には，ヤベオオツノジカ（Sinomegaceros yabei）とヘラジカ（Alces alces）の2種の大型シカ化石が多量に含まれている．本稿では，体骨の詳細な記載と計測を行い，ヤベオオツノジカとヘラジカの体骨の識別点を初めて明確に示した．またヤベオオツノジカの肢骨を中国産のSinomegaceros 属の種，ならびにアイルランド産のMegaloceros giganteusの骨と比較した．その結果，ヤベオオツノジカは中国産のSinomegacerosよりもはるかに大きく，M. giganteus と同程度の大きさであることを明らかにした． Abstract: Kumaishi-do Cave located in central Japan has yielded a great number of Late Pleistocene mammalian fossils. They contain abundant large-sized cervid fossils, which are assigned to Sinomegaceros yabei and Alces alces. This paper presents detailed descriptions and measurements of the postcranial elements, and for the first time reveals discriminating osteological characteristics between the two species. In this paper also the limb bones of S. yabei are compared with those of the Sinomegaceros species from China and Megaloceros giganteus from Ireland. The comparison clearly indicates that S. yabei is much larger than the Sinomegaceros species from China, and comparable in size to M. giganteus. departmental bulletin paper